2020
DOI: 10.1021/acs.est.0c03468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Estrogenic/Antiestrogenic Activities of Perfluoroalkyl Substances and Their Interactions with the Human Estrogen Receptor by Combining In Vitro Assays and In Silico Modeling

Abstract: The potential estrogenic activities of perfluoroalkyl substances (PFASs) are controversial. Here, we investigated the estrogenic/antiestrogenic activities of PFASs and explored the corresponding interaction mode of PFASs with the estrogen receptor (ER) by combining in vitro assays and in silico modeling. We found that three PFASs (perfluorobutanoic acid, perfluorobutane sulfonate, and perfluoropentanoic acid) exerted antiestrogenic effects by inhibiting luciferase activity, whereas perfluorohexane sulfonate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…While another study describes that EGR3 functions as an intracellular mediator of estrogen signaling mechanism in breast cancer. Bother studies provide vital evidence on the association of EGR3 with cancer (Li et al, 2020). In the current study, we found that EGR3 was a highly enriched gene and exhibited a similar expression pattern in both datasets i.e., GSE66359 and GSE45216.…”
Section: Discussionsupporting
confidence: 61%
“…While another study describes that EGR3 functions as an intracellular mediator of estrogen signaling mechanism in breast cancer. Bother studies provide vital evidence on the association of EGR3 with cancer (Li et al, 2020). In the current study, we found that EGR3 was a highly enriched gene and exhibited a similar expression pattern in both datasets i.e., GSE66359 and GSE45216.…”
Section: Discussionsupporting
confidence: 61%
“…Liu et al found that PFOS could increase mRNA expression of PPARγ, CCAAT/enhancer-binding protein-α (C/EBPα), lipoprotein lipase, and leptin [ 37 ]. Furthermore, animal and in vitro studies have shown that certain PFAS, including PFOA and PFOS, have estrogenic activity and directly interact with estrogen receptors (ERs) [ 38 , 39 , 40 , 41 , 42 , 43 ]. ERs play an important part in energy balance, glucose homeostasis, and lipid metabolism [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERs play an important part in energy balance, glucose homeostasis, and lipid metabolism [ 44 , 45 ]. Research has indicated that PFAS may disturb transcription mediated by ERs and interfere with ER signaling pathways [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in genes related to estrogenic pathways could also be observed [ 29 ]. Additionally, PFHxS has been showed to be able to exert estrogenic effects [ 45 ]. Thus, the increase in blastocyst rate and cell count seen here could potentially be due to an estrogenous effect exerted by PFHxS, while higher concentrations of PFHxS may cause suppressed development.…”
Section: Discussionmentioning
confidence: 99%